Developing A Dual-Tier Model For LLP Governance In Malaysia - Hamizah Abdul Rahman; Ravindran Nadarajan; Zuhairah Ariff Abd Ghadas; Mohd Shahril Nizam Mohd Radzi; Rabiatul Adawiyah Mohd Ariffin (Universitas Airlangga, 2026)
A limited liability partnership (LLP) is a new type of business entity in Malaysia, established by the Companies Commission of Malaysia through the Limited Liability Partnership Act (LLPA) in 2012. This study adopted a doctrinal approach through an examination of related legislation and examines the proposed dual-tier model concept of corporate governance in Malaysia, focusing on the legal provisions of LLP. The paper evaluates a dual-tier model and presents arguments for its suitability for LLP corporate governance. It also reviews the responsibilities of the corporate governance committee in developing clear policies and procedures for regulating new LLP structures. The study’s relevance lies in its potential to offer a conceptual framework that defines and evaluates the governance structure within the LLP landscape. It also aims to highlight the benefits and challenges associated with implementing such a governance model, contributing to a more comprehensive understanding of optimal governance practices for LLP. The study’s outcome enriches the understanding of LLP and provides valuable insights for policymakers, practitioners, and regulatory bodies, enhancing governance practices and facilitating informed decision-making within LLP.